Validitas instrumen tes keterampilan berpikir kritis pada materi virus di fase E SMA/MA - Alifda Putri Meivinia; Ardi Ardi; Zulyusri Zulyusri; Helsa Helsa (JRTI (Jurnal Riset Tindakan Indonesia), 2023)
Validity is the extent to which a test can reliably measure the intended construct. This research aims to describing critical thinking skills test instruments on virus material. The data collection technique used is descriptive statistical analysis. Data analysis used the Gregory test content validation technique. The validation results in Table 1 show that the total score of validator 1 is 50 and the score of validator 2 is 54. With a total score of 52. So the average score of validator 1 is 3.33 and validator 2 is 3.6. The Knowledge, Language and Construct Aspects in the expert validity questionnaire show that the 50 items as a whole are categorized as quite relevant with an average score of 3.46. It can be concluded that the item instrument on virus material has very high validity based on the Gregory Test with a score of 0.8 – 1 = Very high validity.Keywords:  Validity, Critical Thinking, Virus, Descriptive.